Qualitative Perceptions of Dapivirine VR Adherence and Drug Level Feedback Following an Open-Label Extension Trial. (1st April 2021) - Naidoo, Kalendri; Mansoor, Leila E.; Katz, Ariana W. K.; Garcia, Morgan; Kemigisha, Doreen; Morar, Neetha S.; Zimba, Chifundo C.; Chitukuta, Miria; Reddy, Krishnaveni; Soto-Torres, Lydia; Naidoo, Sarita; Montgomery, Elizabeth T.
Abstract : Background: There continues to be a need for HIV prevention options that women can initiate and use autonomously. The dapivirine vaginal ring (VR) has been shown to have a favorable safety profile and reduce the risk of HIV-1 acquisition. We report on women's experiences with VR adherence during the MTN-025/HIV Open-label Prevention Extension (HOPE) study and responses to Residual Drug Level (RDL) results. Setting: Ten women at each of the 6 HOPE research sites in Lilongwe, Malawi; Durban (2 sites) and Johannesburg, South Africa; Kampala, Uganda; and Chitungwiza, Zimbabwe, were randomly selected (n = 60). Methods: After confirmation of eligibility criteria, in-depth interviews were conducted where available RDL results were presented. Results: Many women with low RDL release measurements deflected blame onto other factors (the ring, the drug, and faulty testing machines) and distrust of the testing method. The disclosure of RDL results enabled some users to discuss their challenges experienced (fear of partner objections, perceived side effects, and removals during menses). Consistent users reported important motivators (support from others, protection from HIV, and enhanced sexual experiences from the VR). Conclusion: The VR provided a sense of security for some women; however, adherence was still challenging for others regardless of it being a female controlled, long-acting HIV prevention technology. Adherence measurements may not be sustainable in the real-world implementation of the VR, although they can be seen as a benefit as they provide a better understanding of actual product use and provide women with a platform to discuss their experiences.